PENGELOLAAN PEMBIAYAAN MURABAHAH NASABAH UMKM BPRS AMANAH INSANI DI MASA PANDEMI COVID-19 - Ollavega Aurelia (2021)
In March 2020, Indonesia was declared a case of COVID-19 for the first time and implemented Large-Scale Social Restrictions. This causes the performance of the BPRS to decrease due to the ability to pay for MSMEs that receive murabahah financing, which results in an increase in the NPF value. Thus, the purpose of this study is to find out how the quality of the murabahah financing assets of BPRS Amanah Insani during the COVID-19 pandemic for MSME customers and to find out how to manage MSME customers at BPRS Amanah Insani based on murabahah contracts during the COVID-19 pandemic. This research was conducted at the BPRS Amanah Insani in Bekasi, West Java. The method used is descriptive qualitative with case study type. The data collection techniques used were semi-structured interviews, participatory observation with passive participation, and documentation. Data analysis techniques used for data reduction, data presentation, as well as drawing conclusions and levers. The data validity technique used is source triangulation and theoretical triangulation. The results showed that the quality of murabahah financing assets for MSME customers of BPRS Amanah Insani during the pandemic decreased due to the declining business, customer performance, and ability to pay for MSME customers and an increase in NPF in 2020. The management was by implementing financing restructuring for MSMEs with growth prospects. COVID-19 pandemic by rescheduling.